Implementasi Video Pembelajaran dalam Meningkatkan Kualitas Belajar Siswa di Sekolah Dasar: Studi Literatur (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
Advancements in digital technology have triggered various innovations in teaching methods, including the use of video as a learning tool. This paper aims to investigate in depth how the application of video in the learning process can improve the quality of education for elementary school students through a literature review approach. Data were obtained from scientific journals from the last five years and relevant books from the last ten years. The research indicates that the use of video in learning has a positive effect on enhancing conceptual understanding, student motivation, learner engagement, and overall learning achievement. Appropriate, engaging video use that aligns with the development of elementary school-age children can be one of the ways to tackle educational challenges in the 21st century.